A49 Modeling the dynamics of genetic cooperativity in the brain of huntington's disease mice. (September 2018) - Bigan, Erwan; Nair, Satish Sasidharan; Lejeune, François-Xavier; Fragnaud, Hélissande; Parmentier, Frédéric; Verny, Marc; Aaronson, Jeff; Rosinski, Jim; Néri, Christian
Abstract : Gene deregulation has been associated with several neurodegenerative diseases (NDs) and modeling genome-wide data such as transcriptomic data has provided holistic models of ND progression on a gene expression level. However, the consequences of gene deregulation on the temporal dynamics of gene-gene interaction systems (genetic cooperativity) is poorly understood in NDs. Using a multi-layer network approach, we cross-integrated three families of networks describing RNA-seq time series data in Huntington's disease (HD) knock-in mice for reconstructing the dynamics of genetic cooperativity in the brain of these mice based on the consistency and complementarity of edge information in source networks. The resulting model suggests that the HD process may develop as two critical phases of genetic cooperativity, pre-symptomatically in the cortex, involving a neurotransmission response, and symptomatically in the striatum, involving cell survival responses intertwined with cellular senescence and DNA damage responses. These data highlight a 2-step logic for injury/adaptation of the HD mouse brain in which a cortical response for modulating neurotransmission may precede a striatal response for regulating cellular homeostasis synchronous to symptoms.